Multiplicative overlapping Schwarz smoothers for Hdiv-conforming discontinuous Galerkin methods for the Stokes problem - Kanschat, Guido; Mao, Youli (Domain Decomposition Methods in Science and Engineering XXII, 2016)
We present numerical results for a multigrid method employing overlapping Schwarz smoothers in various V-cycle configurations. The method is based on finite element discretizations of the Stokes problem employing Hdiv-conforming velocity spaces and matching pressure spaces. The method acts on the combined velocity and pressure spaces and thus does not need a Schur complement approximation.
Im Titel ist die Zeichenfolge div hochgestellt
Gesehen am 22.01.2018